2013
DOI: 10.15580/gjemps.2013.2.121012320
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of the Inland Waterways Operations and Management on the Development of the Nigerian Maritime Industry

Abstract: This paper looks at the nature, characteristics, scope, impact, effects of inland water ways and to ascertain the relativity of the inland waterways operation and management on the development of the Nigerian Maritime Industry at large with much focus on the inland coastal shipping (cabotage) Act of 2003.This paper was modeled on the premise that looked at both primary and secondary sources of information in its data collection. The primary data was obtained from various responses to quantitative and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This study showed that the inland water transportation sector in Nigeria is been bedeviled by a wide range of maritime safety hazards including; use of incompetent boat operators, poorly constructed jetties, presence of waste materials (plas- Ezenwaji, (2010) [19]; and Obed, 2013 [20]; who found in their various studies…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the inland water transportation sector in Nigeria is been bedeviled by a wide range of maritime safety hazards including; use of incompetent boat operators, poorly constructed jetties, presence of waste materials (plas- Ezenwaji, (2010) [19]; and Obed, 2013 [20]; who found in their various studies…”
Section: Discussionmentioning
confidence: 99%
“…Obed, 2013;Obeta, 2014 in their studies stressed that poor waterway signs lead to many accidents due to navigational disruption. These find-ings are consistent with the findings of the National Inland Waterways Authority (NIWA, 2010) [23]; Obed (2013); and Obeta (2014), but disagree with the findings of Akogun (2014), which suggested that boat operation could be learned as a craft and not only through academic qualification.The study has also identified several unhealthy safety practices which have contributed to the underdevelopment and nose dive of the sector including; no compliance to established safety code of conduct in jetties such as adherence to drug and alcohol policy, safety briefs were rarely conducted before take-off, journey management forms were handled trivially, personal floatation devices (life jacket) were not adequately provided and were not properly worn.…”
mentioning
confidence: 99%
“…With secured water routes; field investigations revealed that inland water transport, chiefly deltaic areas of Lagos, Rivers, Bayelsa and Akwa Ibom, helps rural development. Many academic scholars notable among whom are Fellinda (2006), Ojile (2006), Ezenwaji (2010), Adejare, Nwilo, and Opaluwa (2011), Achumba et al, (2013), Obed (2013), Essien and Adongoi (2015), and Okonkwo et al, (2015) did works on concerns and challenges of maritime security threats. The studies could not consider the current security issues and challenges prevailing in now Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that 'the quality, cost and efficiency of these services influence the trading environment as well as the overall costs linked with transport the international trade of goods. Ogunsanya [2000] explained that special consideration should be taken into account as logistical solutions for the inland waterways ports and Jetty in Nigeria have the following features:-Usoro [2003] and Obed [2013] reported that despite the fact that Nigeria has about 3000 kilometres of inland waters, six major ports and ten crude oil terminals, and several inland ports in Onitsha, Oguta, Opobo, Lokoja, Baro, Jebba, Ayietoro, Epe, etc, in the year 2000, only 139 indigenous marine vessels (less than 6%) were involved in this traffic with a cargo throughput of 441,031 tons (about 1%. ) they concluded that indigenous shipping companies do not own any vessel for deep-sea trade and a few that participate operate the vessels on charter.…”
Section: Introductionmentioning
confidence: 99%